Investigating the effects of influenza virus on alternative cleavage and polyadenylation - Louey, A (2018)
Influenza viruses are a major threat for global health causing both seasonal epidemics and occasional global pandemic outbreaks. While the host has several ways to combat viral infections by activating innate immunity and inducing apoptosis, influenza has evolved many strategies to counter antiviral defences of the host cell. One relevant strategy requires non-structural protein NS1, which is dynamic and interacts with a diverse range of viral and cellular factors to antagonise host antiviral defence and facilitate viral replication. Amongst the cellular factors, NS1 interacts and inhibits cleavage and polyadenylation specificity factor 30 (CPSF30). CPSF30 plays a central role in polyA (pA) site recognition and, interestingly in plants, pA site selection. Therefore, inhibition of CPSF30 compromises host 3’end processing and may affect alternative cleavage and polyadenylation (APA). Furthermore, while APA has been implicated in antiviral responses in herpes simplex virus (HSV-1) and vesicular stomatitis virus (VSV) infection, the potential impact on APA of host transcripts during influenza infection has not been explored. APA plays a fundamental role in regulating transcriptome complexity and gene expression in eukaryotes. Over 70% of human genes undergo alternative polyadenylation, which is resulted from alternative usage of multiple cleavage and polyadenylation (pA) sites found in the 3’UTR (3’UTR- APA) or in the upstream coding region (CR-APA). 3’UTR length modulation through APA affects gene expression regulation by altering the incorporation of cis-regulatory elements that may mediate messenger RNA stability, localisation and translatability. Global shifts in UTR length have been identified in different cell types and cell conditions; however many aspects of gene expression regulation remain unclear. This thesis develops a consistent infection time course experiment, where the necessary controls for robust efficient infections and post-infection controls to determine biologically relevant periods were considered. Combining deep sequencing, subcellular fractionation and molecular biological techniques, the focus of this project assesses the dynamics of infection, the impact of Influenza A/WSN/33 infection on shifting APA profiles in A549 lung epithelial cells, their contributions to gene expression regulation, and physiological impact on host shut-off and host response. Additionally, in order to delineate the mechanism involved in inducing APA, CPSF30 knockdown and transient NS1 over expression experiments were established to mimic infection. Overall this thesis demonstrates influenza A has the ability to hijack the host nuclear and cytoplasmic mRNA pool, but fails to efficiently export viral mRNA to the cytoplasm late in infection. Efficient infection of A549 cells induces significant APA profile changes in both nuclear and cytoplasmic fractions with the majority being independent from the effects of other stresses such as osmotic shock. Physiologically relevant genes that exhibit APA during infection can contribute to gene and protein expression regulation. Furthermore, NS1 mediated abrogation of CPSF30 during infection has been demonstrated to be responsible for APA changes in a small but physiological relevant subset of genes that regulate host immune responses and promote viral propagation.